2019
DOI: 10.7759/cureus.3907
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Consistency between Claims and References Referred to in Pharmaceutical Advertising Brochures in the Kingdom of Saudi Arabia

Abstract: Drug advertisement brochures (DABs) contain claims that are often supplemented by references in medical literature. Several studies have evaluated the DABs as they are commonly distributed by drug companies to practicing physicians. The objective of this study is to assess the consistency between the claims and references referred to in the DABs in Saudi Arabia. DABs were collected from medical practitioners in Riyadh, Saudi Arabia. Authors developed a protocol to be followed for quality assessment of the DABs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These findings were different compared to other studies where a higher percentage of claims made by DAs were supported by appropriate references. 1,15,25 A Spanish review showed that in 44% of the claims for which a reference was cited, the referenced studies did not support the claim. 13 Analysis as per WHO ethical criteria showed that all DAs had mentioned the generic names, brand names, active drug per dosage forms and their approved therapeutic uses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were different compared to other studies where a higher percentage of claims made by DAs were supported by appropriate references. 1,15,25 A Spanish review showed that in 44% of the claims for which a reference was cited, the referenced studies did not support the claim. 13 Analysis as per WHO ethical criteria showed that all DAs had mentioned the generic names, brand names, active drug per dosage forms and their approved therapeutic uses.…”
Section: Discussionmentioning
confidence: 99%
“…14 These criteria are in accordance with the HAI criteria and also with a recent article. 15 A standard approach was used to code the advertisements. The DAs were independently analyzed by the first and second authors who then met, compared notes and arrived at a consensus, if required.…”
Section: Methodsmentioning
confidence: 99%